Dual Color Sensors for Simultaneous Analysis of Calcium Signal Dynamics in the Nuclear and Cytoplasmic Compartments of Plant Cells - Kelner, Audrey; Leitão, Nuno; Chabaud, Mireille; Charpentier, Myriam; de Carvalho-Niebel, Fernanda (Frontiers in Plant Science, 2018)
Spatiotemporal changes in cellular calcium (Ca2+) concentrations are essential for signal transduction in a wide range of plant cellular processes. In legumes, nuclear and perinuclear-localized Ca2+ oscillations have emerged as key signatures preceding downstream symbiotic signaling responses. Förster resonance energy transfer (FRET) yellow-based Ca2+ cameleon probes have been successfully exploited to measure the spatiotemporal dynamics of symbiotic Ca2+ signaling in legumes. Although providing cellular resolution, these sensors were restricted to measuring Ca2+ changes in single subcellular compartments. In this study, we have explored the potential of single fluorescent protein-based Ca2+ sensors, the GECOs, for multicolor and simultaneous imaging of the spatiotemporal dynamics of cytoplasmic and nuclear Ca2+ signaling in root cells. Single and dual fluorescence nuclear and cytoplasmic-localized GECOs expressed in transgenic Medicago truncatula roots and Arabidopsis thaliana were used to successfully monitor Ca2+ responses to microbial biotic and abiotic elicitors. In M. truncatula, we demonstrate that GECOs detect symbiosis-related Ca2+ spiking variations with higher sensitivity than the yellow FRET-based sensors previously used. Additionally, in both M. truncatula and A. thaliana, the dual sensor is now able to resolve in a single root cell the coordinated spatiotemporal dynamics of nuclear and cytoplasmic Ca2+ signaling in vivo. The GECO-based sensors presented here therefore represent powerful tools to monitor Ca2+ signaling dynamics in vivo in response to different stimuli in multi-subcellular compartments of plant cells.